A conceptual framework for research on subjective cognitive decline in preclinical Alzheimer's disease. Issue 6 (2nd May 2014) - Jessen, Frank; Amariglio, Rebecca E.; van Boxtel, Martin; Breteler, Monique; Ceccaldi, Mathieu; Chételat, Gaël; Dubois, Bruno; Dufouil, Carole; Ellis, Kathryn A.; van der Flier, Wiesje M.; Glodzik, Lidia; van Harten, Argonde C.; et al.
Abstract: There is increasing evidence that subjective cognitive decline (SCD) in individuals with unimpaired performance on cognitive tests may represent the first symptomatic manifestation of Alzheimer's disease (AD). The research on SCD in early AD, however, is limited by the absence of common standards. The working group of the Subjective Cognitive Decline Initiative (SCD‐I) addressed this deficiency by reaching consensus on terminology and on a conceptual framework for research on SCD in AD. In this publication, research criteria for SCD in pre‐mild cognitive impairment (MCI) are presented. In addition, a list of core features proposed for reporting in SCD studies is provided, which will enable comparability of research across different settings. Finally, a set of features is presented, which in accordance with current knowledge, increases the likelihood of the presence of preclinical AD in individuals with SCD. This list is referred to as SCD plus .